SARS-CoV-2 infections in "less visible" hospital staff: The roles and safety of environmental services and allied health professionals - Sebastian Jensen; Marianna Traugott; Dariga Ramazanova; Helmuth Haslacher; Patrick Mucher; Thomas Perkmann; Maren Jeleff; Ruth Kutalek; Christoph Wenisch; Richard Crevenna; Galateja Jordakieva (Elsevier, 2023)
Background: During the early SARS-CoV-2 pandemic, all healthcare workers had specific and essential functions. However, environmental services (e.g., cleaning staff) and allied health professionals (e.g., physiotherapists) are often less recognised inpatient care. The aim of our study was to evaluate SARS-CoV-2-infection rates and describe risk factors relevant to workplace transmission and occupational safety amongst healthcare workers in COVID-19 hospitals before the introduction of SARS-CoV-2-specific vaccines. Methods: This cross-sectional study (from May 2020 to March 2021, standardised WHO early-investigation protocol) is evaluating workplace or health-related data, COVID-19-patient proximity, personal protective equipment (PPE) use, and adherence to infection prevention and control (IPC) measures, anti-SARS-CoV-2-antibody status, and transmission pathways. Results: Out of n = 221 HCW (n = 189 cleaning/service staff; n = 32 allied health professionals), n = 17 (7.7 %) were seropositive. While even SARS-CoV-2-naïve HCW reported SARS-CoV-2-related symptoms, airway symptoms, loss of smell or taste, and appetite were the most specific for a SARS-CoV-2-infection. Adherence to IPC (98.6 %) and recommended PPE use (98.2 %) were high and not associated with seropositivity. In 70.6 %, transmission occurred in private settings; in 23.5 %, at the workplace (by interaction with SARS-CoV-2-positive colleagues [17.6 %] or patient contact [5.9 %]), or remained unclear (one case). Conclusions: Infection rates were higher in all assessed 'less visible' healthcare-worker groups compared to the general population. Our data indicates that, while IPC measures and PPE may have contributed to the prevention of patient-to-healthcare-worker transmissions, infections were commonly acquired outside of work and transmitted between healthcare workers within the hospital. This finding emphasises the importance of ongoing education on transmission prevention and regular infection screenings at work.